The Dynamics of the Times and the Complexity of LeadershipThe President in Modern Government - Andi Fahmi Riski; Andi Fadil Tri Putra; Hasfitrayani Hasfitrayani; Nurhikmah Nurhikmah; Nurul Anggraeni; Andi Santri Syamsuri (Indonesian Journal of Civic and Law Studies (IJCL), 2025)
This study discusses the dynamics of the times and the complexity of presidential leadership in modern government, which faces various multidimensional challenges, ranging from technology, politics, economics, socio-culture, the environment, to political integrity. The digital revolution and artificial intelligence present opportunities as well as risks that require adaptive and visionary leadership. In addition, rapidly changing global geopolitical dynamics require strategic diplomacy to maintain national interests and domestic stability. Economic fluctuations and the need for inclusive development add to the complexity of policy-making. Social polarization, hoaxes on social media, and environmental challenges such as climate change reinforce the demand for inclusive, transparent, and sustainable leadership. The main focus is also given to strengthening political integrity and legitimacy by adapting to the aspirations of the younger generation. Effective leadership strategies include strengthening the bureaucracy, public-private collaboration, and integrating short-and long-term interests to achieve sustainable development. This study uses a systematic and critical literature analysis method to provide a comprehensive overview of the challenges and strategic solutions in the development of future national leadership. The results of this study are implicative for the formation of more advanced, responsive, and sustainable presidential leadership in the era of modern governance.